1994
DOI: 10.1111/j.1474-8673.1994.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional β‐adrenoceptors in the left atrium of normotensive and hypertensive rats

Abstract: 1. The aim of the study was to characterize the functional beta 1-and beta 2-adrenoceptors of the rat left atrium and to investigate how these functional beta-adrenoceptor responses were altered in hypertension. The contractile responses of the left atrium from Wistar-Kyoto (WKY) and spontaneously hypertensive (SH) rats to isoprenaline, T-0509 and procaterol were characterized. Subsequently, the effects of selective beta 1-(bisoprolol) and beta 2 (ICI 118,551)-adrenoceptor antagonists were investigated on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…Circulating adrenaline can enhance the neuronal outflow of noradrenaline by stimulating presynaptic neuronal facilitatory b 2 -adrenoceptors [43]. Indeed, in pre-hypertensive and hypertensive SHR, there is increased functional b 2 -adrenoceptor response [44,45]. Furthermore, pre-weaning treatment of SHR with the b-blocker carvedilol reduced blood pressure during treatment and attenuated the subsequent development of hypertension [46].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating adrenaline can enhance the neuronal outflow of noradrenaline by stimulating presynaptic neuronal facilitatory b 2 -adrenoceptors [43]. Indeed, in pre-hypertensive and hypertensive SHR, there is increased functional b 2 -adrenoceptor response [44,45]. Furthermore, pre-weaning treatment of SHR with the b-blocker carvedilol reduced blood pressure during treatment and attenuated the subsequent development of hypertension [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, Doggrell and Surman [44] have shown that functional ß-adrenoceptors in the left atrium of hypertensive rats were not altered. In our left atrial strips, eugenosedin-A antagonized the isoproterenol-induced positive inotropic effects in WKY and SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, changes in the in vitro pharmacodynamic properties of β‐adrenoceptor antagonists have rarely been studied in experimental hypertension. Doggrell and Surman 20 have demonstrated that the dissociation constant of bisoprolol to left atrial β 1 ‐adrenoceptors was not altered in SHR.…”
Section: Discussionmentioning
confidence: 98%